Good grief [videorecording (DVD)] - Rued, Emily; Rued, Emily; Whitworth, Johnny, 1975-; Thayer, Brynn, 1949- (Freestyle Digital Media, 2026)
After her mother dies, a grief-stricken artist spirals through loss, love, and self-discovery in this raw, darkly funny dramedy.